(untitled) (Indo-MathEdu Intellectuals Journal, 2024)
This article aims to find out the role of pkm uhn medan students in creating clean villages and smart communities in Banjaran Raya village, Langkat Regency. The type of approach used is qualitative through descriptive methods. This method is used to directly describe the factual conditions that occur in the field. Data collection is done through observation, interviews, and documentation. Data analysis is carried out qualitatively through data reduction, data presentation, and conclusions. The results of data analysis show that maintaining environmental cleanliness can be applied by the community. This can be proven from the community’s activeness in carrying out mutual assistance to maintain the cleanliness of the village environment